GLOMO - Global Mobility Model: Beschreibung und Ergebnisse - André Kühn; Patrick Novinsky; Wolfgang Schade (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2014)
– The development of both, emerging markets as well as the already establish markets (USA, Japan, Europe), is highly relevant for future success of the export-oriented German automotive industry. This paper describes the so called Global Mobility Model (GLOMO) based on the system dynamics approach, which simulates the future development of car sales by segment and drive technology. The modularized model contains population, income and GDP development in order to describe the framework in the most important markets (USA, Japan, EU, Brazil, Russia, India, China and South Africa). According to the changes in framework conditions within these countries, worldwide car sales will nearly double up to 2030 (120 Mio. cars a year), with the most dynamic development in the Chinese market. The simulation results also show that - depending on the chosen scenario - a 40 %- share of alternative drive technologies within the worldwide car sales in 2030 seems to be possible.
urn:nbn:de:0011-n-3070066
Keywords: 330